Pendampingan Keluarga Balita Stunting di Posyandu Banjar Nyawah, Desa Selulung, Kecamatan Kintamani - Dewa Ayu Agung Alit Suka Astini; Anak Agung Made Semariyani; Ni Putu Diah Witari; Komang Trisna Sumadewi; Luh Gede Evayanti; Fransiscus Fiano Anthony Kerans; Ida Kurniawati; Anak Agung Ayu Asri Prima Dewi; Ni Wayan Diana Ekayani (Warmadewa Minesterium Medical Journal, 2025)
Stunting remains one of the major public health challenges in Indonesia, with long-term impacts on human resource quality. In Banjar Nyawah, five families were identified with toddlers who are either stunted or at risk of stunting. This condition is driven by inadequate nutritional intake far below the Recommended Dietary Allowance (RDA), limited knowledge and skills of mothers in preparing healthy meals, and the families’ low economic status. This Community Partnership Program (PKM) aims to improve child nutritional status and empower family economies through two main strategies: (1) provision of high-protein nutrition packages, along with education and training on preparing healthy meals using local ingredients; and (2) training on producing packaged loloh kunyit (a traditional turmeric-based herbal drink) as a family income-generating product. The program was implemented in stages through socialization, education, training, distribution of nutrition packages, and evaluation. The educational component focused on the "My Plate" concept, balanced nutritional parenting practices, and hands-on preparation of nutritious toddler meals. Evaluation was conducted by comparing pretest and posttest results, which showed an improvement in participants’ knowledge and skills after the program. The results indicate that educational and productive approaches can have a positive impact on improving children's nutritional status and enhancing family economic potential.